Customer Relations Management Strategy (CRM) in Handling Customer Service Complaints To Increase Customer Satisfaction - Afif Nur Rahmadi; Sudarmiatin, Sudarmiatin; Budi Eko Soectjipto; Yudiarto Perdana Putra; Rana Saifullah Hassan (International Journal of Management Science, 2024)
This research evaluates the implementation of Customer Relationship Management (CRM) strategies at PT Nasmoco Kaligawe Semarang, focusing on handling customer service complaints to enhance satisfaction. Using a descriptive qualitative approach and SWOT analysis, the study gathered primary data through interviews and field observations, alongside secondary data from literature and documentation. The findings indicate that PT Nasmoco's CRM strategies possess notable strengths, such as a strong Toyota brand image and effective promotional activities. However, weaknesses include prolonged service times and relatively high service costs compared to competitors. Opportunities for improvement are highlighted in the company's official Toyota repair shop status, which can be leveraged to attract more customers. Threats identified include intense competition and challenges with service timeliness. The research suggests that PT Nasmoco should address these weaknesses by increasing staffing in the CRM division, enhancing communication channels, and developing a smartphone application to streamline service booking and reduce customer complaints